Patterns of susceptibility in an outbreak of Bordetella pertussis: Evidence from a community-based study - Moore, David M (Pulsus Group Inc, 2002)
OBJECTIVE: To describe an outbreak of Bordetella pertussis and to assess which factors were associated with the development of clinical pertussis in children and adults during the outbreak. DESIGN: A case series was described to define the epidemiology of the pertussis outbreak. A school-based survey of children was used to measure the incidence of clinical pertussis over the previous six months. Vaccination records from the local public health facility were used to look at the relationship between age and vaccination parameters, and susceptibility to clinically diagnosed pertussis. A cross-sectional survey of teachers, parents and some hospital workers was used to assess these associations in adults. SETTING: An outbreak of pertussis in an isolated northern community in British Columbia. POPULATION STUDIED: All children in the community who attend daycare, kindergarten or school, and their parents were surveyed. In addition, some health care workers and mothers of preschool children were surveyed. MAIN RESULTS: A total of 31 suspected cases of pertussis were identified over a three-month period. Ninety per cent of the affected children who had available vaccination records had received four or five doses of pertussis vaccine. Sixty per cent of the town's 209 children returned completed surveys. Of these, 69% had available vaccination records. Thirty-six children (28%) reported symptoms that fit the case definition for pertussis over the previous three months. Attack rates were highest for the group of children aged 10 to 14 years. In a multivariate logistic regression analysis, receiving prophylactic medication and an increased number of years from the last vaccine dose were found to be significant predictors for developing pertussis. Thirty-four per cent of the estimated 291 adults in the community returned completed surveys. The attack rate of pertussis in the adults was only 9%. Being a member of the school staff and/or having a household contact with pertussis were significant predictors of developing pertussis. CONCLUSIONS: Immunity to pertussis appears to wane during childhood. Peak susceptibility appears to be during early adolescence. Adults do not seem to be at greater risk than adolescents for developing the disease, but it seems unlikely that this is due to better immunity. Rather, it is probably related to a lower risk of exposure to pertussis and a lower rate of progression to symptomatic disease when adults are infected.